Study of a common control strategy for grid-connected shunt active photovoltaic filter without DC/DC converter. (June 2021) - Alali, Mohamad Alaa Eddin; Sabiri, Zakaria; Shtessel, Yuri B.; Barbot, Jean-Pierre
Abstract: This paper partially validates a published patent. A common control strategy for grid-connected three-phase three-wire shunt active filter with photovoltaic generator, without DC/DC converter, that compensates the electrical grids perturbations (harmonics, reactive power, unbalanced currents, etc.) is studied. The maximum power of the photovoltaic generator is generated and fed to the grid/loads. In the proposed common control strategy, with an advanced phase locked loop, an extended instantaneous real and imaginary powers method is proposed to identify, jointly or individually, all current perturbations, as well as the current at maximum photovoltaic power in phase with the grid fundamental voltage. Furthermore, the DC voltage control loop is the maximum power-based, unlike the conventional control loop that is based on the maximum current, which allows easier integration of the maximum photovoltaic power into the extended instantaneous powers algorithm. Besides, the current control law is implemented in a single control loop only that simplifies the design. In this work, with the absence of the DC/DC converter, which makes the overall structure more reliable and economical, the output of the adapted perturb & observe algorithm is the voltage at maximum power. Finally, the studied structure is validated via real textile factory case study while using the experimental real measurements provided by power quality analysers. Indeed, under the new modelling strategy of 97% accuracy, the maximum photovoltaic current is injected while ensuring a unity power factor, balanced current with 0.16% of unbalance factor, as well as almost 1% total harmonic distortion of current at the grid side.